GEOMETRIC CONSTRAINTS AND TANGENTIAL AND RADIAL STRESSES OF ROTATING DISCS WITH VARIABLE THICKNESS - Prahasto, Toni (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
This article presents an algorithm along with Scilab codes to calculate radial and tangential stresses in rotating disc with varying thickness. The continuous change of thickness is represented by stepped; discrete ones.The geometry of disc is represented by two arrays, each of whose elements represents the radius and the thickness respectively. The stresses arise due to combination of rotation and prescribed pressures at the outer and inner radiuses of the disc. The stresses are limited to linearly elastic cases; loadings and rotation causing either non-linear elastic or plastic strains are beyond the scope of this work. Linear inequality onstraints on the values of the radiuses are prescribed in order to prevent overlapping of radiuses, and thus maintain the validity of the disc geometry. Codes are designated for Scilab for ease of use.